Bacterial community including opportunistic pathogens dynamics in a chlorine tablet-dosed chloraminated service reservoir and reticulation pipes. (September 2020) - Bal Krishna, K C; Sathasivan, Arumugam; Cox, Peter; Doolan, Corinna
Abstract: This study reports even minimal changes of chloramine (measured as total chlorine) residual by chlorine tablets dosing in a service reservoir modify the bacterial community composition. The study was carried out by characterising the bacterial community composition in bulk water samples collected from the inlet, outlet, and downstream of a service reservoir. A regular dose of chlorine tablets to increase the chloramine by about 0.15 mg/L in the service reservoir increases total chlorine to ammonia nitrogen ratio and induces locally breakpoint chlorination within the proximity of the chlorine tablets. This, in turn, selects the specific bacterial groups despite smaller changes in the chloramine concentration. The dominated bacterial genera (87.1–93.8%) in the service reservoir were Methylobacterium and unclassified Rhizobiales whereas Methylobacterium, unclassified Rhizobiales, and Hyphomicrobium dominated (71.8–93.4%) downstream distribution pipelines of the service reservoir. E.Coli was not detected during the study period. Total chlorine residuals, nitrification, and temperature did not influence the presence/absence including the relative abundances of the majority of the opportunistic pathogens (characterized using the MiSeq Illumina platform). However, the presence of Burkholderia and Legionella increased at low total chlorine residuals and high temperatures in a small number of samples. Although this might indicate the importance of higher total chlorine residuals, more studies are needed to confirm if it is a valid strategy/or if there is health significance. Graphical abstract: Image 1 Highlights: Chlorine tablets dosing in the reservoir may induce localised breakpoint chlorination. Even a smaller increase in chloramine residual is sufficient to change the bacterial community in the reservoir. Alphaproteobacteria was the highly dominant bacteria in chlorine tablets dosed system. Chloramine residuals & nitrification status don't impact the occurrence of majority of opportunistic pathogens.